2002
DOI: 10.3201/eid0806.01-0331
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Differences Between Cyclosporiasis and Cryptosporidiosis in Peruvian Children

Abstract: We compared the epidemiologic characteristics of cyclosporiasis and cryptosporidiosis in data from a cohort study of diarrhea in a periurban community near Lima, Peru. Children had an average of 0.20 episodes of cyclosporiasis/year and 0.22 episodes of cryptosporidiosis/year of follow-up. The incidence of cryptosporidiosis peaked at 0.42 for 1-year-old children and declined to 0.06 episodes/child-year for 5- to 9-year-old children. In contrast, the incidence of cyclosporiasis was fairly constant among 1- to 9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
1
16

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 20 publications
8
91
1
16
Order By: Relevance
“…In contrast, a longitudinal study from Peru consistently identified more asymptomatic infections than symptomatic infections. 4,27,29 Both longitudinal studies from Brazil and Israel and those from Guinea-Bissau 32 and Uganda 2 identified more persistent (diarrhea lasting ≥ 14 days) diarrhea than acute diarrhea (diarrhea lasting less than 4 days). However, no persistent diarrhea was found in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a longitudinal study from Peru consistently identified more asymptomatic infections than symptomatic infections. 4,27,29 Both longitudinal studies from Brazil and Israel and those from Guinea-Bissau 32 and Uganda 2 identified more persistent (diarrhea lasting ≥ 14 days) diarrhea than acute diarrhea (diarrhea lasting less than 4 days). However, no persistent diarrhea was found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of children in developing countries have reported multiple infections in 14-30% of cases. [27][28][29] Longitudinal studies from Brazil 30 and Israel 28 and cross-sectional studies on children with diarrhea from Uganda and Mexico 2, 31 have reported a greater prevalence of symptomatic infections than asymptomatic infections. In contrast, a longitudinal study from Peru consistently identified more asymptomatic infections than symptomatic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Peaks in Cryptosporidium prevalence appear to correspond with warmer seasons in temperate and tropical climates (Bern et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Most families immigrated from either the Peruvian Andes or coastal communities in the 1980s (15). Data collected by the non-profit organization AB PRISMA demonstrated that 97% of homes had electricity, 48% had toilets, and 64% had a household water connection (16). AB PRISMA has operated a field research site in Pampas since 1986.…”
Section: Settingmentioning
confidence: 99%